LEGO®-Based Therapy in School Settings for Social Behavior Stimulation in Children with Autism Spectrum Disorder: Comparing Peer-Mediated and Expert Intervention - Luciana Oliveira Angelis; Fernanda Tebexreni Orsati; Maria Cristina Triguero Veloz Teixeira (Brain Sciences)
Background: LEGO®-based therapy is a social development protocol that uses LEGO® activities to support the development of a wide range of interaction skills, enhancing prosocial behaviors and mitigating the challenges associated with mental health difficulties and behavioral issues commonly observed in children with autism spectrum disorder (ASD). Objectives: This study aimed to explore the effects of LEGO®-based therapy on the social behavior and mental health of children with ASD, comparing stimulation mediated by expert and stimulation mediated by non-autistic peers. This study was approved by the Ethical Committee at Mackenzie Presbyterian University, ensuring adherence to ethical standards throughout the research process. Methods: This study involved 18 children with ASD, levels 1 or 2, with an intelligence quotient (IQ) above 70, and three typically developing peers, intelligence quotient (IQ) above 80, aged between 5 and 8 years old, of both sexes. Participants were randomized into three groups for stimulation (stimulation mediated by expert, by a non-autistic peer and control group). The measures were the Wechsler Abbreviated Scale of Intelligence, the Strengths and Difficulties Questionnaire (parent and teacher versions), the Inventory of Difficulties in Executive Functions, Regulation, and Aversion to Delay—Child Version, the Developmental Coordination Disorder Questionnaire, the Autism Behavior Checklist, and the Autistic Behavior Inventory. Results: After 14 sessions of 45 min in school settings, the participants of both groups (mediated by experts and non-autistic children) showed significant gains on social behavior. A statistically significant difference was observed between baseline sessions and probes (χ2 (5) = 25.905, p < 0.001). These gains were maintained in both follow-up points, 30 and 90 days after the completion of the stimulation sessions. Additionally, maladaptive behavior showed a significant decline when compared pre- and post-intervention. These improvements were sustained during follow-up assessments at 30 and 90 days. Conclusions: The results suggest that a structured intervention combined with peer-mediated stimulation may be an effective method for promoting adaptive and prosocial behaviors in children with ASD.